If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x(x+13)=-12
We move all terms to the left:
x(x+13)-(-12)=0
We add all the numbers together, and all the variables
x(x+13)+12=0
We multiply parentheses
x^2+13x+12=0
a = 1; b = 13; c = +12;
Δ = b2-4ac
Δ = 132-4·1·12
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{121}=11x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-11}{2*1}=\frac{-24}{2} =-12x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+11}{2*1}=\frac{-2}{2} =-1
| 6x6=36 | | 3.14x6x=4396 | | 5x+3(x+4)=9 | | 45x+80x=8040 | | 5-12y=3y | | 45+x+x=80 | | 50=2u+10 | | 1.4(y-5)-0.2=0.5(6y-8) | | 1x+72=32 | | Y=2.6x+3.1 | | 1/3(-9x-3)=11 | | 4d=3d–7 | | 4^(x+1)+2^(x+1)=72 | | 5^9/5^t=5^-3 | | 12*2(7r=)6 | | 2(-8-k)=-2k-11 | | 4x+5=9x-155x | | 11y=4÷11 | | |x-6|=8 | | Y=3x+-27 | | x+1/4=13 | | 3(5x−7)=24 | | 6x-2=5(4x+8) | | 2x(x-1)=x(x+1) | | 6(x-8)=2(x+6) | | 5x-(-4x)=-27 | | -4(-3y)-5y=21 | | x+1/5=4/5 | | 2(3x+5)=4(X+3)-4 | | 7x+5=-50 | | -4(5)+5y=-30 | | 0.60x+8=0.75(x+10) |